CREATIVITY IN MARKETING IS THE MOST DEMANDED SOFT SKILL TODAY - PROTSYSHYN, Yuliia (Herald of Khmelnytskyi National University. Economic sciences, 2022)
The article analyzes the concepts of "creativity" and "creativity", their relationship. Very often, people mix these concepts or use them as synonyms, without thinking about the true meaning of the words. Conducted marketing research "Creative Marketing" using a survey of marketing students, which made it possible to understand the need to study the discipline "Creative Marketing Studio" and introduce it into the educational process (namely, the Department of Marketing of WUNU). Creativity is not something people are born with, it is a skill that can be learned and can only be improved with practice. The human brain is like muscles that need to be pumped - in this case, with the help of cognitive exercises. The importance of mastering creativity skills in marketing as the most sought-after soft skills today has been proven. Creativity is one of the most important skills of the 21st century that marketing graduates will need for career success after graduation. For modern professions, especially those related to innovation, creativity is needed - the ability, based on accumulated experience and knowledge, to generate new ideas and methods that optimize the work process or create a unique product. Creative thinking is needed by many, especially in business, advertising, science, art, and politics. Now, in many job offers, you can find messages that the employer needs creative people for various positions. The research of the global job search platform LinkedIn "Top 5 most in-demand personal qualities and professional skills that the company requires from its employees" was analyzed, as well as the rating of personal qualities of people for successful work in business, which was formed at the World Economic Forum in Davos. It is worth paying attention that creativity is needed not only in science or professional activity, but also in everyday life.